2012
DOI: 10.1055/s-0031-1301268
|View full text |Cite
|
Sign up to set email alerts
|

Unterschiede bei Gesundheitsrisiken, Morbidität und gesundheitlicher Versorgung zwischen Kindern GKV- bzw. PKV-versicherter Eltern: Ergebnisse aus dem Kinder- und Jugendgesundheitssurvey (KiGGS)

Abstract: Health risks are usually greater among GKV-insured children as compared with PKV-insured. Concerning morbidity, these differences can mainly be explained by differences in national origin and SES. Efforts aimed at reducing these health differences should therefore focus on risks associated with migration and low SES. In addition, differences concerning risk factors such as smoking could not be explained by differences in national origin and SES. Thus, there seems to be a general need for more preventive measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 12 publications
0
8
1
5
Order By: Relevance
“…Both statutory and private health insurances fully reimburse recommended vaccinations. The authors of a large population-based cross-sectional study found no difference in the proportions of undervaccinated children when comparing children from parents with statutory and private health insurance [36]. Thus, we assume comparable VC and VE in children not covered by the IIS.…”
Section: Discussionmentioning
confidence: 87%
“…Both statutory and private health insurances fully reimburse recommended vaccinations. The authors of a large population-based cross-sectional study found no difference in the proportions of undervaccinated children when comparing children from parents with statutory and private health insurance [36]. Thus, we assume comparable VC and VE in children not covered by the IIS.…”
Section: Discussionmentioning
confidence: 87%
“…Insgesamt fanden sich Unterschiede hinsichtlich soziodemografischer und gesundheitsbezogener Merkmale nicht nur zwischen PKV und GKV, sondern es zeigt sich häufig ein Gradient zwischen der AOK, sonstigen gesetzlich und privat Versicherten. In der Forschung zur sozialer Ungleichheit hat man sich bisher hingegen nahezu ausschließlich auf Unterschiede zwischen GKV und PKV konzentriert [68][69][70][71][72][73]. Auch wenn eine noch detailliertere Auswertung oftmals durch zu kleine Fallzahlen erschwert wird, dürfte eine zusätzliche Unterscheidung der AOK in jedem Fall möglich sein.…”
Section: Implikationen Für Die Forschung Zu Sozialen Und Regionalen Uunclassified
“…In this regard, the authors of a bivariate and multivariate analysis in a population-based cross-sectional study found no difference in proportions of undervaccinated children from statutorily and privately health insured parents. 19 Our sampling method for the analysis of ASHIP data excludes individuals with potential suboptimal VC such as children who receive their first vaccination very late or children of parents who completely refuse vaccinations. In addition, mobile groups like Roma/Sinti populations that are difficult to be reached by standard immunization programs 20 are also possibly underrepresented in our approach resulting in a potentially positive sampling bias and a slight VC overestimation.…”
Section: Discussionmentioning
confidence: 99%